46 Enhanced pro-inflammatory systemic response and potential viral factor in coronary artery ectasia. (5th October 2017) - Sharif, Z; Boles, U; Johansson, A; Wiklund, U; David, S; Henein, MY
Abstract : Background: Coronary artery ectasia (CAE) is a common coronary artery disorder associated with adverse outcome but with determined pathophysiology. In the present study we sought to examine the systemic chronic inflammatory response that might associate CAE with respect to normal. Methods: Plasma samples from 16 patients with coronary artery ectasia (median age 64.9 ± 7.3 years, 12 male) and 71 matched controls (64.8 ± 8.6 years, 31 males) with normal coronary arteries. Samples were analysed at Umea university Biochemistry Laboratory, Sweden, using the V-PLEX Proinflammatory Panel 1 (human) Kit. Statistically significant differences (p<0.05) between patients and controls were determined using Mann-Whitney U-tests. Results: The CAE patients had significantly higher systemic levels of INF and TNF IL-1 and IL-8 (p = 0.007, 0.01, 0.001 and 0.002 respectively), while the levels of IL-2 and IL-4 were lower (P < 0.001 for both). The systemic levels of IL-10, IL-12 p and IL-13 did not differ significantly between patients and controls. None of these markers was significantly different between patients with Pure (n=6) and mixed (n=10) CAE with minimal atherosclerosis. Conclusion: These results indicate an enhanced systemic pro-inflammatory response in CAE, irrespective of additional atherosclerosis. The profile of this response indicates activation of macrophages, as well as possible involvement of a viral factor. The raised IL-8 levels may suggest additional evidence for angiogenesis.